Prozessorientierte Integration von Softwarekomponenten durch XML-basierte Workflow-Modelle - Lütkemeier, Björn; Thöne, Sebastian (Proceedings of the Fachwissenschaftlicher Informatik-Kongress (Informatiktage 2001), Bad Schussenried (Germany))

Compositional Modeling of Reactive Systems Using Open Nets - Baldan, Paolo; Corradini, Andrea; Ehrig, Hartmut; Heckel, Reiko (Proceedings of the conference on Concurrency Theory (CONCUR 2001), Aalborg (Denmark))

Consistent Design of Embedded Real-Time Systems with UML-RT - Küster, Jochen; Stroop, Joachim (Proceedings of the conference on Object-Oriented Real-Time Distributed Computing (ISORC 2001), Magdeburg (Germany))

Improving the Agent-Oriented Modeling Process with Roles - Depke, Ralph; Heckel, Reiko; Küster, Jochen (Proceedings of the Fifth International Conference on Autonomous Agents (AGENTS 2001), Montreal (Canada))

Modellierung von Prozessen mit UML und Realisierung durch eine Internet-Agentenplattform - Depke, Ralph; Heckel, Reiko (Proceedings of the 9. Kolloquium Software-Entwicklung für Internet und Intranet, Ostfildern (Germany))

Rule-Based Specification of Behavioral Consistency Based on the UML Meta-model - Engels, Gregor; Heckel, Reiko; Küster, Jochen (Proceedings of the conference on The Unified Modeling Language, Modeling Languages, Concepts, and Tools (UML 2001), Toronto (Canada))
Object-oriented modeling favors the modeling of object behavior from different viewpoints and at different levels of abstraction. This gives rise to consistency problems between overlapping or semantically related submodels. The absence of a formal semantics for the UML and the numerous ways of employing the language within the development process lead to a number of different consistency notions. Therefore, general meta-level techniques are required for specifying, analyzing, and communicating consistency constraints. In this paper, we discuss the issue of consistency of behavioral models in the UML and present techniques for specifying and analyzing consistency. Using meta-model rules we transform elements of UML models into a semantic domain. Then, consistency constraints can by specified and validated using the language and the tools of the semantic domain. This general methodology is exemplified by the problem of protocol statechart inheritance.

A methodology for specifying and analyzing consistency of object-oriented behavioral models - Engels, Gregor; Küster, Jochen; Groenewegen, Luuk; Heckel, Reiko (Proceedings of the 8th European Software Engineering Conference (ESEC 2001) and 9th ACM SIGSOFT Symposium on the Foundations of Software Engineering (FSE-9), Vienna (Austria))
Object-oriented modeling favors the modeling of object behavior from different viewpoints and the successive refinement of behavioral models in the development process. This gives rise to consistency problems of behavioral models. The absence of a formal semantics for UML models and the numerous possibilities of employing behavioral models within the development process lead to the rise of a number of different consistency notions. In this paper, w e discuss the issue of consistency of behavioral models in the UML and present a general methodology how consistency problems can be dealt with. According to the methodology, those aspects of the models relevant to the consistency are mapped to a semantic domain in which precise consistency tests can be formulated. The choice of the semantic domain and the definition of consistency conditions can be used to construct different consistency notions. We show the applicability of our methodology by giving an example of a concrete consistency problem of concurrent object-oriented models.

Towards UML-based Analysis and Design of Multi-Agent Systems - Geiger, Christian; Flake, Stephan; Küster, Jochen (Proceedings of International NAISO Symposium on Information Science Innovations in Engineering of Natural and Artificial Intelligent Systems (ENAIS 2001), Dubai (United Arab Emirates))

Graph Transformation as a Meta Language for Dynamic Modeling and Model Evolution - Heckel, Reiko; Engels, Gregor (Proceeding of International Special Session on Formal Foundations of Software Evolution (FFSE 2001, co-located with the Conference on Software Maintenance and Reengineering), Lisbon (Portugal))

Towards Dynamic Meta Modeling of UML Extensions: An Extensible Semantics for UML Sequence Diagrams - Hendrik Hausmann, Jan; Heckel, Reiko; Sauer, Stefan (Proceedings of the IEEE Symposia on Human Centric Computing Languages and Environments (HCC 2001), Stresa (Italy))